Stabilisasi Tanah Ekspansif Dengan Campuran Zeolite - Herdiman Herdiman, Heru; Budiman, Dedi (JITSi : Jurnal Ilmiah Teknik Sipil, 2022)
Abstract— Expansive soil is a term used for soils that have a high potential for expansion or shrinkage due to changes in water content. The soil in Cilopang Village, Banjarwaringin Village, Salopa District, Tasikmalaya Regency is suspected of having expansive properties, judging by the visual nature and the facts on the road field which is located at every change of the rainy season the soil will expand and cause flooding and road collapses, whereas during the dry season the soil will shrinks and causes the ground to crack dry. This study aims to analyze the physical and mechanical properties of the original soil and to analyze the physical and mechanical properties of the mixed soil that has been treated with Zeolite. The method used is for physical properties including water content, specific gravity, bulk density, and Atterberg limit. For mechanical tests include Proctor, and California Bearing Ratio. Having obtained from the research results Liquid Limit = 57% and Plastic Limit = 28.20% the results are Plastic Index = 29.11%, including clay with high expansivity and After adding zeolite of 10% results from Liquid Limit = 49% and Plastic Limit = 41.56% yield, namely Plastic Index = 7.16%. Plasticity index values and soil types, obtained plasticity index values of 7-17, including silty clay soils with moderate expansiveness. CBR test results show an increase in value from 10.5% to 16%. Keywords — Zeolite, Atterberg Limit, Plastic Insect, Clay Soil   Abstrak— Tanah ekpansif (expansive soil) adalah isilah yang digunakan pada tanah yang mempunyai potensi pengembangan atau penyusutan yang tinggi oleh pengaruh perubahan kadar air. Tanah di Kampung Cilopang, Desa Banjarwaringin, Kecamatan Salopa Kabupaten Tasikmalaya diduga memiliki sifat ekspansif, melihat dari sifat visual dan fakta di lapangan jalan yang berada di lokasi setiap pergantian musim penghujan tanah akan mengembang dan mengakibatkan banjir serta jalan amblas, sedangkan pada musim kemarau tanah akan menyusut dan mengakibatkan tanah retak-retak kering. Penelitian ini bertujuan menganalisa sifat fisik dan mekanis tanah asli serta menganalisis sifat fisik dan mekanis tanah campuran yang telah diberi Zeolite. Untuk metode yang gunakan adalah untuk sifat fisik meliputi kadar air, berat jenis, berat isi, dan atterberg limit. Untuk uji mekanis meliputi Proctor, dan California Bearing Ratio. Setelah didapatkan dari hasil penelitian Liquid Limit = 57% dan Plastis Limit = 28,20% hasil yaitu Index Plastis = 29,11%, termasuk tanah lempung dengan ekspansifitas tinggi dan Setelah ditambahkan zeolite sebesar 10% hasil dari Liquid Limit = 49% dan Plastis Limit = 41,56% hasil yaitu Index Plastis = 7,16%. Nilai Indeks Plastisitas dan Macam Tanah, didapat nilai Indeks Plastisitas 7 – 17, termasuk tanah lempung berlanau dengan ekspansifitas sedang. hasil uji CBR menunjukkan peningkatan nilai dari 10.5% menjadi 16%. Kata kunci — Zeolite, Atterberg Limit, Indek Plastis, Tanah Lempung